Multi-scale Analysis and Control Structure Design for Biotechnological Processes - Nandong, Jobrun; Tade, Moses (The American Institute of Chemical Engineers-AIChE, 2008)
In this paper, a novel methodology of multi-scale analysis and control structure design is proposed for typical multi-scale biotechnological processes. This methodology combines the concepts of factorial design, multiprojection analysis and control relevant metric. The effectiveness of this methodology in handling multi-scale variables including micro-scale phenomena is demonstrated using two examples, which are two-stage distributed feed (TSDF) extractive alcoholic fermentation and recycled micro-aerobic fermentation processes. In both examples, the control structure designs resulting from the proposed methodology shows superior robustness/performance than the arbitrarily chosen control structures.